Error correction : how essential it is for teachers and what to do when students commit them repeatedly - Abrego Sánchez, Suyapa Imelda; Erazo, David Nehemías; Valiente Durán, Giovanni Wilfredo (2024)
The final work of the Bachelors of Arts in Teaching demands teachers be well prepared not only by practice but also by a deep theory study. English language teachers must be led from theory to practice and vice versa when it comes to improve the art of teaching on a daily basis. It is very necessary for teachers to analyse as well as contrast what happens on the classrooms every day. The importance of not taking for granted issues that seem simple leads to critical thinking teachers who, in turn, can keep on contributing to the discussion of complex matters such as the one presented in this paper work. If teachers go beyond theory and become able to contrast it with accurate supporting after real world practice, they can whether revoke what somebody says, or reinforce and support what somebody establishes. Just by doing this, teachers can contribute to the changes our educational society requires when teaching a foreign language